Feminist Collections, v.20, no.2 (winter 1999) - (:unkn) unknown (My University, 1999)
Subtitle: A Quarterly of Women's Studies Resources. 46p.
Contents: FROM THE EDITORS. BOOK REVIEWS: Devil in a Blue Dress: Women, Inherent Evil, and the Sin of Witchcraft, by Susan E. Taylor. Amazons in the War on Poverty, by Rebecca Young. Women on the (Mostly Male) Jobsite: Still Struggling, by Jocelyn Riley. In Search of Adventure: Women of Daring and Duty, by Thomas P. Maloney. FEMINIST VISIONS: Women Objectified: Gender, Violence, and Mass Media, by Jill M. Duquaine. WORLD WIDE WEB REVIEWS: Witches on the Web: A Review of Some Scholarly Sites on Witches by Fabienne Baider aad Anita Liang. The Old Religion: Websites on Wicca, by Gail Wood. Single Parent Support Groups and Information on the Web, by Barbara Walton. COMPUTER TALK: Compiled by Linda Shult. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard. PERIODICAL NOTES: Compiled by Linda Shult. ITEMS OF NOTE: Compiled by Christina Stross. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Witchcraft; War on Poverty; Non-traditional Jobs; Violence and Mass Media; Single Parent Support Groups